Distributed containment control of linear multi-agent systems using output information - Hu, Guoqiang (2013)
This paper concerns the distributed containment problem of multi-agent systems with linear or linearized node dynamics under a directed communication topology. A new class of distributed control protocol based only on the relative outputs of neighboring agents is designed and utilized to achieve containment. Under the assumptions that each agent is stabilizable and detectable, and for each follower there exists at least one leader that has a directed path to that follower, it is theoretically proved that containment in the closed-loop multi-agent system can be guaranteed. A multi-step containment protocol design procedure is further provided. At last, the convergence rate of the containment in multi-agent systems is discussed. Finally, a simulation example is given to verify the effectiveness of the theoretical results.